Quality Education Efforts during COVID 19 Pandemic Growth Mindset - Yani Supriani (Green Publisher Indonesia, 2023)
During the Covid 19 pandemic, students had low motivation and enthusiasm because they were not ready to face the various difficulties caused by the pandemic. Students who have a growth mindset will have an impact on efforts to build quality education, especially during the Covid 19 pandemic and studies on growth mindset in the scope of education in Indonesia are still limited. The purpose of this research is to foster a growth mindset in order to achieve the Sustainable Development Goals (SDGs) goals in the form of efforts to build quality education during the Covid 19 pandemic. This research method uses the literature study method (research results review). The growth mindset has a very important role in building strong student personalities during the learning process during the Covid 19 pandemic. The quality of education has a major influence on other fields, and by having a growth mindset the younger generation can help the community and provide positive enthusiasm to face any situation, at any time, and to anyone. The slightest participation from youth who have a growth mindset will be able to bring about this change. From this study it resulted that a growth mindset can realize the achievement of the SDGs goals in the form of quality education efforts during the Covid 19 pandemic.